Isolation and identification of the angiotensin-I converting enzyme (ACE) inhibitory peptides derived from cottonseed protein: optimization of hydrolysis conditions. Issue 1 (1st January 2019) - Gao, Dandan; Zhang, Fumei; Ma, Zhongren; Chen, Shien; Ding, Gongtao; Tian, Xiaojing; Feng, Ruofei
ABSTRACT: Peptides derived from food proteins have exhibited significant antihypertensive effects without side effects. In this study, the cottonseed protein was hydrolyzed by papain for preparing peptide with angiotensin I converting enzyme (ACE) inhibitory activity. The influence of hydrolysis temperature (33°C, 40°C, and 47°C), pH (6.5, 7.0, and 7.5), and enzyme to substrate (E/S) ratio (0.9%, 1.2%, and 1.5%) on the degree of hydrolysis (DH) and ACE-inhibitory activity were analyzed. The hydrolysis conditions were further optimized by central composite design (CCD) and response surface methodology (RSM). The DH of cottonseed protein and ACE inhibitory rate of hydrolysates reached 25.7% and 88.2%, respectively, under the optimal hydrolysis conditions (hydrolysis temperature 39°C, pH 7.5, and E/S ratio 1.04%). We further separated the cottonseed protein hydrolysates (CPH) using a combined strategy of ultrafiltration membrane bioreactor system, sephadex G-25 gel filtration chromatography and reversed-phase high-performance liquid chromatography (RP-HPLC). An ACE inhibitory peptide, named as FII-2-P, with ACE inhibitory IC50 value of 46.7 μg/mL, was obtained. MALDI-TOF-TOF mass spectrometry analysis revealed that the molecular weight of FII-2-P was 763.4 Da and its amino acids sequence was Phe-Pro-Ala-Ile-Gly-Met-Lys. These results demonstrated that the cottonseed protein is a potential source of ACE inhibitory ingredients to be used in the development of functional foods.